Evaluasi Manajemen Rantai Pasok Usaha Pembuatan Kapal Pinisi: Sebuah Penerapan Konsep Ekonomi Biru - Handayani, Sri; Nasir, Laode Arahman; Biantara, Dheny (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2025)
T The Pinisi boat is a maritime cultural heritage of Indonesia originating from Bulukumba Regency, South Sulawesi. However, the sustainability of the Pinisi boat-building industry faces various challenges in the shipyard business. This study aims to evaluate the supply chain in the Pinisi boat-building industry and design a more effective, efficient, and sustainable supply chain management strategy using the blue economy approach. The research method used is a qualitative approach, with data collected through semi-structured interviews with shipyard business owners and Pinisi boat craftsmen. The collected data were analyzed using content analysis, thematic analysis, and constant comparative analysis with the aid of NVivo 15 software. The results show that supply chain management in this industry is still not optimal, particularly in raw material procurement, workforce management, and marketing. Additionally, foreign intervention in the shipyard business has led to market price imbalances and poses a threat to the industry’s sustainability. Therefore, a blue economy-based strategy is needed, including more sustainable raw material management, increased access to financing for craftsmen, and the use of digital technology for marketing and distribution. By implementing these strategies, the Pinisi boat-building industry is expected to continue growing and providing greater economic benefits to coastal communities. Keywords: Pinisi, supply chain, blue economy